A Comparative Analysis of Contemporary Phrase Structure Grammar of English and Burmese - Silananda; Kanokkamalade, Veerakarn; Kittipanyo, Phrama Somchai (วารสารพุทธจิตวิทยา, 2026)
This research had the objectives to 1) to investigate the contemporary phrase structure grammar of Burmese language, 2) to compare the contemporary phrase structure grammar of English and Burmese languages, and 3) to analyze the similarities and differences between contemporary phrase structure grammar of English and Burmese language. This research design was a qualitative study using the methodological procedure for a study gathering through documentary and in-depth interviews. The researcher employed tools such as questionnaires and interviews, by utilizing the phrase structure in the Burmese Language used by respondents. The result exposed as follows: The findings directly address the three primary objectives of the study by providing a systematic examination of Burmese contemporary phrase structure grammar, a cross-linguistic comparison with English, and an analysis of their structural similarities and differences. The analysis demonstrates that Burmese phrase structure is fundamentally organized around the relationship between the head and its modifiers, comparable to English, yet governed by distinct syntactic principles. Burmese noun phrases typically follow a Modifier + Head configuration, whereas English commonly exhibits a Determiner + Modifier + Head pattern. Verb phrases in Burmese are predominantly verb-final, in contrast to the verb-medial structure associated with English subject–verb–object alignment. Adjective and adverb phrases also display divergent structural positioning, with Burmese permitting greater flexibility in post-head modification. Furthermore, although prepositional phrases in both languages fulfill similar semantic roles, Burmese structurally realizes these relationships through postpositions rather than prepositions. In addition, Burmese employs classifiers and grammatical particles to encode grammatical relations that English generally expresses through prepositional and inflectional mechanisms.